Super binary vector system enhanced transformation frequency and expression level of polyhydroxyvalerate gene in oil palm immature embryo - Ahmad Fuad, Fazia Adyani; Ismail, I; Sidik, N.M.; Zain , C.R.C.M.; Abdullah , R. (Asian Network or Scientific Information, 2008)
The aim of this study was to compare the efficiency of two transformation vectors: binary and super binary vector in the process of gene transfer and expression in oil palm tissues. Two transformation vectors, namely pFA2 (binary vector, ~24.4 kb) and pFA3 (super binary vector, ~39.4 kb) that contains four essential genes (bktB, phaB, phaC and tdcB) to produce polyhydroxyvalerate have been successfully constructed. The two transformation vectors and pMR505, which used as a control were later transformed into oil palm tissues mediated by Agrobacterium tumefaciens. Oil palm immature embryos were cocultivated with Agrobacterium. tumefaciens that carry pFA2, pFA3 and pMR505 separately and also contain the higromycin phosphotransferase (hpt) and α-glucuronidase (gus) genes. GUS assay was carried out on putatively transformed immature embryos as an indicator of successful gene transfer. From the analysis, high percentage of transient GUS expression ranging from 52.6-85.7, 70.5-96.7 and 80.9-93.8% for pFA2, pFA3 and pMR505, respectively were obtained from putative transformed immature embryos. The successful integration of bktB (1.2 kb), phaB (0.8 kb), phaC (1.0 kb) and tdcB (0.9 kb) genes into the immature embryos genome were confirmed by PCR analysis. Relative quantification through real-time PCR analysis indicates that the expression of PHBV gene in oil palm immature embryos transformed with pMR505 is 7 times higher than non transformed immature embryo, followed by transformed with pFA2 (2 times) and pFA3 (0.7 times), respectively. Thus, this data suggest the efficiency of super binary vector compared to binary vector in transferring foreign genes and enhancing its expression in oil palm tissues.